PENGEMBANGAN PRODUK WISATA ALAM KAWAH WURUNG, KABUPATEN BONDOWOSO - Fajar Rasyiidi Hidayat; Yusri Abdillah; Luchman Hakim (Jurnal Administrasi Bisnis, 2018)
Wurung Crater is one of the tourist attractions in Bondowoso. Wurung Crater has beautiful natural scenery as well as some tourism potentials, but the elements of tourist attraction such as something to see, something to buy and something to do, have not been explored as the design of product development. Tourism product development is expected to attract tourists to conduct tourism activities in Wurung Crater, as well as to invite related stakeholders such as local people and government to participate, so that it can succeed the development of natural tourism product of Wurung Crater. Based on the results of the research tourism potential that can be used as a tourist product in Wurung Crater based on the wishes of the visitor are Mountain bike tour, which is tour around some interesting places in Wurung Crater by mountain bike. Village tour, the tour enjoys the village life of coffee workers and learns how to manage coffee. This Research suggest that it needs a brodder involvement of the local community expecially for providing homestay, a tour guide and tour site manager. The local government should provide more community services such as Human Resources training, conduct marketing activities, and build facilities and infrastructure. Keywords: Product Development, Role of Government, Community Roles, and Kawah Wurung. ABSTRAK Kawah Wurung merupakan salah satu daya tarik wisata yang berada di Kabupaten Bondowoso. Kawah Wurung memiliki pemandangan alam yang indah serta beberapa potensi wisata, tetapi unsur atraksi wisata seperti something to see, something to buy dan something to do belum banyak digali sebagai desain dari pengembangan produk. Pengembangan produk wisata di harapkan mampu menarik wisatwan untuk melakukan kegiatan wisata di Kawah Wurung, serta mengajak para pemangku kepentigan terkait seperti masyarakat setempat dan pemerintah untuk berpartisipasi, sehingga dapat mensukseskan pengembangan produk wisata alam Kawah Wurung. Berdasarkan hasil penelitian potensi wisata yang dapat dijadikan produk wisata di Kawah Wurung berdasarkan keinginan dari wisatawan adalah Mountain bike tour, yaitu tur mengelilingi beberapa tempat menarik di Kawah Wurung dengan menggunakan sepeda gunung. Village tour, yaitu tur menikmati kehidupan desa para pekerja kopi dan belajar cara pengelolaan kopi. Hasil penelitian ini menyarankan agar terdapat peran lebih dari masyarakat sekitar dalam hal menyediakan penginapan, menjadi pemandu wisata dan pengelola lokasi wisata. Pada sisi yang lain, pemerintah dapat melakukan pelatihan Sumber Daya Manusia, melakukan aktivitas pemasaran, serta membangun sarana dan prasarana. Kata Kunci: Pengembangan Produk, Peran Pemerintah, Peran Masyarakat, dan Kawah Wurung